SOCIAL CULTURE IN THE STORY OF TENGGER MASKS - Resdianto Permata Raharjo; Haris Supratno (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The Topeng Tengger puppet is a puppet that shows by a movement. The movement is combined with stories produced by the puppeteer. Stories in puppet masks are various, ranging from banner stories, Mahabarata, legends, and community life. The uniqueness of the Tengger mask puppet has a mystique that is not shared by other shadow puppets. The mask of Bethara Kala is a mystical mask that cannot be used by everyone. Mr. Sutama can use it, because he is a descendant of the mask wearers of Bethara at the time. Ki Lebari is the mastermind of the mask show, as well as Mr. Sutama, He is a hereditary mastermind who is still known by the Wonokerso villagers as the only puppeteer who can tame the Bethara Kala mask. The location of the Tengger mask puppet itself is in Wonokerso village, Sumber District, Probolinggo Regency. The story that is presented when using the Bethara Kala mask is a story from "Bethara Guru Krama" the story is used only to complicated, if there is no ruwatan mask and the story will not be played. The meaning contained in the story told by Ki Lebari is in accordance with the reality in Wonokerso village. The socio culture produced by the Tengger community is a reflection of the story that is believed by the Wonokerso villagers. The preservation of culture in the Wonokerso village has received less attention from the Probolinggo government. The lack of socialization about the existence of the Tengger puppet mask made them struggle to be recognized by Indonesian. People only know the beauty of Mount Bromo and the Kasada ceremony.